PENGETAHUAN DAN SIKAP KONSUMEN DALAM MEMBELI SUSU KEDELAI ECERAN DI BANDAR LAMPUNG - Rizki Ramadhan; Yaktiworo Indriani; Umi Kalsum (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The purposes of this research were to know the consumer knowledge of retail soy milk and the attitude of consumers towards retail soy milk. The research was conducted by survey method in a traditional market in Bandar Lampung which was chosen on purpose. The total samples were 100 consumers who had been buying retail soy milk when were found and be chosen using sampling convenience technique.  The data was collected in February until March 2014.  The research results showed that the knowledge of retail soy milk consumers were diverse and averagely in the middle level. Most consumers had good knowledge on the freshness, price, volume, and calcium content attributes of retail soy milk. The analysis results of the Fishbein multiattribute toward consumer attitudes showed that the attitude scores (Ao) of easiness of obtaining the product got the highest value of 2.02, followed by the attribute of benefits 1.75.  The attitude score (Ao) of retail soy milk was 9.50; this was in the positive category and also highly favored by consumers. Key words : attitude, knowledge, fishbein multiatribut, soy milk